+0  
 
+1
84
1
avatar+588 

Solve for r.

f / r+ a = n + k

adore.nuk  Feb 28, 2018
 #1
avatar+7155 
+3

f / r2 + a   =   n + k

                                    Subtract  a  from both sides of the equation.

f / r2   =   n + k - a

                                    Multiply both sides of the equation by  r2 .

f   =   r2(n + k - a)

                                    Divide both sides of the equation by  (n + k - a)

f / (n + k - a)  =  r2

                                    Take the ± square root of both sides.

±√[ f / (n + k - a) ]  =  r

 

r  =  ±√[ f / (n + k - a) ]

hectictar  Feb 28, 2018

14 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.